COVID-19 HEALTHCARE WORKER BURNOUT: WORK ENVIRONMENT AND WORKLOAD AS INFLUENCING FACTORS - Ardhianti, Ulva; Sary, Fetty Poerwita (Faculty of Economics and Business, University of Pasundan, 2024)
The COVID-19 pandemic is an unexpected event. Hospitals must maintain the burnout level of health workers to maintain optimal energy in providing health services. One way to keep the burnout level of health workers in X Hospital is to pay attention to the work environment and workload. The non-probability sampling method used in this research is quantitative with descriptive research analysis. The analytical method used is multiple linear regression. The results showed that the work environment variables were not good, and workload and burnout were in a relatively high category. Results based on a coefficient of determination of 18.2% burnout in health workers caring for COVID-19 patients at Hospital X are influenced by the physical work environment and workload. This study concluded that the physical work environment and workload significantly affected the burnout of health workers treating COVID-19 patients at X Hospital.